2009
DOI: 10.1007/s10549-009-0690-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the association between CYP17 T34C polymorphism and the risk of breast cancer: meta-regression and subgroup analysis

Abstract: A number of studies have been investigated the association between CYP17 T34C polymorphism and the risk of breast cancer; the results of these studies are inconsistent, however. This fact implies that the effect of CYP17 T34C polymorphism on susceptibility to breast cancer may be modified by other risk factors. In order to provide a more definitive conclusion, a full meta-analysis combining and summarizing 24 studies was first performed. Both traditional method and Bayesian approach were applied. Odds ratio wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…There are 3 meta-analyses that have reported an association between the CYP17A1 T27C polymorphism and breast cancer risk, all published in 2010 [12,22,23]. These meta-analyses included 24-43 studies from different populations and showed no association between the CYP17A1 T27C polymorphism and breast cancer, which is in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…There are 3 meta-analyses that have reported an association between the CYP17A1 T27C polymorphism and breast cancer risk, all published in 2010 [12,22,23]. These meta-analyses included 24-43 studies from different populations and showed no association between the CYP17A1 T27C polymorphism and breast cancer, which is in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, a biological justification for the choice of genetic model was required [27]. The procedure to capture the inheritance mode in association studies has been described previously [28]. In brief, k (the ratio of log OR Val/Ala and log OR Ala/Ala ) was determined; the pairwise estimates of the OR of Ala/Ala versus Val/Val (OR Ala/Ala ) and the OR of Val/Ala versus Val/Val (OR Val/Ala ) were performed by carrying out two separate meta-analyses [27].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional and Bayesian meta-analysis procedures have been described previously [28,34]. In traditional metaanalysis, Mantel and Haenszel method and DerSimonian and Laird method were employed in fixed effects and random effects models, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations